2008
DOI: 10.1021/ma702374g
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium Pathway of Spin-Coated Polymer Films

Abstract: Spin-coating is a common method of making thin polymer films. Recent experiments show that polymer films produced by this method are highly nonequilibrated. By monitoring the temporal evolution of the surface structure of freshly spin-cast polystyrene films on Si with molecular weights, 2.3 ≤ M w ≤ 393 kg/mol, we find that the relaxations can be fully accounted for by thermal excitations of surface capillary waves on the film surface. Modeling of the data based on this relaxation scheme leads to excellent agre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
83
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(87 citation statements)
references
References 27 publications
4
83
0
Order By: Relevance
“…The former is consistent with a recent viscosity measurement of 18 nm PS films by time-resolved AFM. 109 If this behavior indeed reflects τ −1 (T), as tentatively suggested by the authors, 108 the physics of thin film T g may require ideas different from the ones suggested so far. On the basis of the above discussions, obtaining a measurement of τ(T) for films much thinner than 20 nm would be important for understanding the anomalous dynamics of polymer films.…”
Section: Concluding Remark and Outlookmentioning
confidence: 86%
“…The former is consistent with a recent viscosity measurement of 18 nm PS films by time-resolved AFM. 109 If this behavior indeed reflects τ −1 (T), as tentatively suggested by the authors, 108 the physics of thin film T g may require ideas different from the ones suggested so far. On the basis of the above discussions, obtaining a measurement of τ(T) for films much thinner than 20 nm would be important for understanding the anomalous dynamics of polymer films.…”
Section: Concluding Remark and Outlookmentioning
confidence: 86%
“…Previous studies have examined the time course of entanglement formation in spin-coated globular polystyrene (PS) thin films on silicon wafers, on which the formation of entanglements was delayed by the substrate effect. [4][5][6][7][8] fewer entanglements than PS films fabricated by normal methods. 9,10 Therefore, globular solids may be temporarily fabricated in the spin-coated PS thin films.…”
mentioning
confidence: 90%
“…The relationship between a and the fractal dimension is a5d f (8) for mass fractals where d f is the mass fractal dimension and a 5 62d s (9) for surface fractals where d s is the surface fractal dimension. 35,36 The a values obtained in this study were in the range 3 < a < 4, which indicated that scattering was from surface fractal geometry.…”
Section: Solid State Properties Mechanical Propertiesmentioning
confidence: 99%
“…In addition, the highly non-equilibrium glassy state of polymeric films can be affected by high spin speeds or rapid solvent evaporation [24,25]. These may cause polymer chains to orient in preferential directions.…”
Section: Introductionmentioning
confidence: 99%